IMPROVE THE INTERETATION OF STUDY SUBJECTS PANCASILA AND CITIZENSHIP EDUCATION BY APPLYING KONSTEXTUAL LEARNING MODEL BERBASIS A TASK IN CLASS INFORMATICS XI SMK BINA ECLECTUS ACADEMIC YEAR 2015/2016 - Hasanudin S. Usman (Universitas Khairun, 2015)
The purpose of this research is to know how to incerease the students’ learning achievement that has been applied learning contextual task-based learning model and to know the influence of contextual learning in the task-based teaching model to improve achievemen and motivation to learn the material pe civis lesson. This research is an action research by theree rounds. Each round consists of four phases. Design activities are observation, and revesion. The subject of the research is XI grade students of Bina Informatika Ternate accademic year 2015/2016. Data obtained in the form of a formative test results, observation sheet teaching and learning activities. The results of the research showed that students’ achivement increased from round I to III that the round 1, (70.00 % ), (92,50 %) 3 cycles, conclusions of this research is the method of cooperatif learning can be a positive influence on students motivation and achievement in material udaya politics in Indonesia. It means that this model can be used as one of the alternative learning for Pkn. Kata kunci: PKn, cooperative learning method